Survey on backdoor attacks targeted on neural network - Qingyin TAN; Yingming ZENG; Ye HAN; Yijing LIU; Zheli LIU (网络与信息安全学报)
According to existing neural network backdoor attack research works, the concept of neural network backdoor attack is first introduced.Secondly, the research status of neural network backdoor attack is explained from three aspects: research development, summary of typical work and classification.Then, some typical backdoor attack strategies are analyzed in detail.Finally, the research status is summarized and the future research directions are discussed.